The Role of Financial Literacy in Students in Increasing Interest in Using Mobile Banking - Ade Ihwani Harahap; Laila Tri Oktavianti; Muhammad Fikri; Herlina Yustati (Yayasan Darussalam Bengkulu, 2023)
This study aims to analyze the extent to which the level of financial literacy in college students affects students' interest in using mobile banking. With a better understanding of the factors that influence students' interest in using mobile banking, it can help develop more effective educational and promotional strategies to increase financial literacy and the use of mobile banking among college students. The data in this study were generated from interviews with several students at the Faculty of Economics and Islamic Business, Fatmawati Sukarno State Islamic University Bengkulu. The number of respondents in this study were 20, namely 10 sharia economics study program students, and 10 sharia banking study program students. From the interviews that researchers have conducted, 90% of respondents have used mobile banking in conducting daily transactions. This mobile banking service is also very easy to access using only a cellphone. In addition, the features available in mobile banking also provide comfort and convenience, such as quick access to balances, transferring funds without having to go to the bank, transaction notifications so that users can see funds in or out of the account, and additional security from two-step verification. The ease of use of the features contained in mobile banking is also one of the reasons that many students are interested in using the mobile banking service, because the mobile banking service can be accessed anytime and anywhere.